Respuesta :

Answer:

1. x = 7

2. x = -5

Step-by-step explanation:

1. Rearrange the equation by subtracting what is to the right of the equal sign from both sides of the equation: 2*x+5*(6*x-9)-(179)=0

Pull out like factors  6x - 9  =   3 • (2x - 3)

 (2x +  15 • (2x - 3)) -  179  = 0

Pull out like factors: 32x - 224  =   32 • (x - 7)

Solve: x-7 = 0

Add  7  to both sides of the equation  = 7

2. Rearrange the equation by subtracting what is to the right of the equal sign from both sides of the equation: -40-(6*x-5*(-4*x-18))=0

Pull out like factors: -4x - 18  =   -2 • (2x + 9)

 -40 -  (6x -  -10 • (2x + 9))  = 0

Pull out like factors:  -26x - 130  =   -26 • (x + 5)

-26 • (x + 5)  = 0

Solve: x+5 = 0

Subtract  5  from both sides of the equation: x = -5

Hope this helps! Please mark as brainliest.

Thanks!

ACCESS MORE